Impact of vanillin on postharvest disease control of apple - Wang, Xiangyu; Zhang, Xuemin; Sun, Meng; Wang, Li; Zou, Yaoyuan; Fu, Lin; Han, Chuanyu; Li, Anqing; Li, Limei; Zhu, Chunyu (Frontiers in Microbiology, 2022)
Apple fruits are susceptible to infection by postharvest fungal pathogens, which may cause fruit decay and severe economic losses. This study investigated the antifungal spectrum of vanillin against common decay pathogens of apple and explored the antifungal mechanisms of vanillin in vitro. In vivo experiments were carried out to evaluate the effects of vanillin on apple postharvest disease control and fruit quality. Moreover, the induced resistance mechanism of vanillin on apple fruit was preliminarily explored. The results showed that vanillin has broad-spectrum antifungal effects, especially on Alternaria alternata. Vanillin could significantly inhibit the growth rate, mycelium biomass, and spore germination of pathogenic fungi by increasing the cell membrane permeability and lipid peroxidation. Importantly, vanillin treatment reduced the incidence of apple decay caused by A. alternata and Penicillium expansum, and contributed to improve fruit quality. Further studies indicated that vanillin could induce elevation in the activities of defense-related enzymes in apple fruit, such as phenylalanine ammonia-lyase (PAL), chitinase (CHI) and β-1,3-glucanase (β-1,3-GA), and increase total phenols and flavonoids contents. Generally, these results suggest that vanillin may contributed to the induced resistance of apple fruits to pathogenic fungi. To conclude, the results of this research provide theoretical foundations for the application of vanillin in the control of apple postharvest decay caused by fungal pathogens.